Developing Model for Diffusion of Farmers’ Innovations for Maximizing Farm Income: Indian Agricultural Research Institute Experiences - Nain, Manjeet Singh; Singh, Rashmi; Mishra, J R; Singh, Anil Kumar (Indian Journal of Extension Education, 2024)
Indian farmers have also been continuously improving available technologies for more efficient and cost effective farming, which resulted in numerous innovations over the generations and helped in improving farming practices ensuring better livelihood options. The action research was carried from 2015 to 2021 to document, verify, scalability testing, developing sharing and scaling mechanism, identifying support mechanism and finally devising scaling mechanism for higher profits, reduced costs, enterprise development, enhanced employment opportunities and capacities, growth and survival. The results of various interventions showed that FLIs were mostly reconfiguration of existing resources giving incremental adjustments. All innovators studied expressed dissatisfaction with the pre-existing economic returns of the farming thus pushing them to innovate. Economic effect of the farmers’ innovations in terms of changes in income, change in savings of stakeholders, change in capital owned and change in credit availability were expressed on an average. The innovations which were economically viable and found sustainable source of funding were able to translate into entrepreneurial ventures having higher income and profits. The conceptual model for scaling farmers’ innovations was found effective on the basis of experiences and interventions.
Keywords: Farmers’ innovations; Scalability; Social media; Networking; Innovators’ meet